Methodology For Calculating Automotive Oil Radiator - E. P. Parlyuk; A. V. Kurilenko (Сельскохозяйственные машины и технологии)
The paper highlights the relevance of the problem of determining the amount of heat supplied by an internal combustion engine to a liquid cooling system when creating typical series of unified heat exchangers for tractor and combine engines (power units). A properly designed cooling system further guarantees the maintenance of the optimal thermal mode for the engine operation. A methodology for calculating the coolant characteristics of the cooling system was proposed in order to prevent possible problems related to increased parts wear, early loss of oil lubricating properties, the engine (individual units) and rubbing parts overheating, a decrease in engine power and a deterioration in the quality of the fuel-air mixture entering the cylinders.Research purpose To develop a methodology for calculating the amount of heat to be dissipated by the oil radiators of a liquid cooling system (lubrication system) being exposed to various load and engine speed modes.Materials and methods It was proposed to determine the amount of heat to be dissipated by the liquid-oil heat exchanger of the engine lube oil cooling system.Results and discussion The calculation method for oil radiators presents the calculation of the heat obtained by oil during the operation of 37-110 kilowatts automotive engines. The heat-dissipating ability of the oil surface is determined. A parameter taking into account the oil radiator heat flow is identified. The graphs of the oil surface and heat flux dependence on the engine power are presented.Conclusions The method for calculating the temperature and dynamic characteristics of the automotive engine cooling system has been developed. It makes it possible to carry out research on the radiator thermal and technical characteristics in various operating modes of machines and coolants of systems, various heat exchanger structural materials (metal, polymer), with an error of 1.5-8.0 percent.